Tunable, conductive, self-healing, adhesive and injectable hydrogels for bioelectronics and tissue regeneration applications. Issue 31 (2nd August 2021) - Panwar, Vineeta; Babu, Anand; Sharma, Anjana; Thomas, Jijo; Chopra, Vianni; Malik, Pinki; Rajput, Swati; Mittal, Monika; Guha, Rajdeep; Chattopadhyay, Naibedya; Mandal, Dipankar; Ghosh, Deepa
Abstract : Conductive hydrogels are attracting considerable interest in view of their potential in a wide range of applications that include healthcare and electronics. Abstract : Conductive hydrogels are attracting considerable interest in view of their potential in a wide range of applications that include healthcare and electronics. Such hydrogels are generally incorporated with conductive materials/polymers. Herein, we present a series of conductive hydrogels (Ch–CMC–PDA), prepared with no additional conductive material. The hydrogels were synthesized using a combination of chitosan, cellulose (CMC) and dopamine (DA). The conductivity (0.01–3.4 × 10 −3 S cm −1 ) in these gels is attributed to ionic conductivity. Very few conductive hydrogels are endowed with additional properties like injectability, adhesiveness and self-healing, which would help to widen their scope for applications. While the dynamic Schiff base coupling in our hydrogels facilitated self-healing and injectable properties, polydopamine imparted tissue adhesiveness. The porosity, rheological, mechanical and conductive properties of the hydrogels are regulated by the CMC-dialdehyde-polydopamine (CMC-D-PDA) content. The hydrogel was evaluated in various bioelectronics applications like ECG monitoring and triboelectric nanogenerators (TENG). The ability of the hydrogel to support cell growth and serve as a template for tissue regeneration was confirmed using in vitro and in vivo studies. In summary, the integration of such remarkable features in the ionic-conductive hydrogel would enable its usage in bioelectronics and biomedical applications.